Elaboração de uma proposta de programação curricular de aulas de Ciências da Natureza via enfoque Ciência, Tecnologia e Sociedade (CTS)-Freire - Maciel, Elton Junior (Universidade Federal de São Carlos, 2023)
Science, in the National Curricular Parameters of Natural Sciences, as emphasized by the Secretariat of Elementary Education of the Ministry of Education, can expand the possibility of social participation and mental development of students, enabling their full capacity to exercise citizenship, as it has an impact directly into people's lives, demystifying and reflecting on habits and behaviors such as caring for environmental impacts and their impact on society. Thinking that Natural Sciences, such an important discipline, is present in schools and educational institutions throughout Brazil, makes us reflect on the responsibility of those in the classroom. The teacher is an important agent for the construction of knowledge, therefore, reflecting on educational perspectives reminds me of Freire and the references linked to the Science-Technology-Society (STS) movement, being the agenda of this work with the objective of developing a proposal of curricular programming for natural science classes using the STS-Freire approach. For this, the study uses Participant Research and, although in an adapted way, critical-transformative education is used as a basis via Generating Themes, therefore Freire's thematic investigation (1987), through the steps systematized by Delizoicov (1982) is present in the study. In addition, Strieder's CTS Reference Matrix (2012), adapted by Almeida (2018), is also used, systematizing the different educational approaches and purposes found in the production on STS Education in the Brazilian context, brought in this study as a background for programming. curriculum. The large number of information collected was systematized in several tables that made it possible to create two examples of Teaching Plan containing, in total, 36 45-minute classes, which revolved around the Generating Theme raised. This material, although there was no possibility of application, constitutes a curricular proposal under the STS-Freire approach. This work demonstrates that, despite the enormous challenges posed by the current educational system, it is still possible to do more for education. Reflecting and acting on the reproduction of conservative pedagogical practices that contribute to keeping society passive, in the face of the advances of the capitalism steamroller, is to fight and resist, even within our limits. Understanding Science, Technology and their relationships with Society, in a critical way, can also be transformative.
Elaboration of a proposal for curricular programming of Natural Sciences classes via the focus on Science, Technology and Society (STS)-Freire
Keywords: Pesquisa Participante; Educação Libertadora; CTS-Freire; Impactos ambientais; Participant Research; Liberating education; Environmental impacts; CIENCIAS HUMANAS::EDUCACAO::CURRICULO